O papel da efetividade da transferência do conhecimento entre a personalidade do profissional de projetos e o sucesso do projeto: um artefato - Araújo, Valdemilson de Assis Alves de (2023)
This thesis had the general objective of proposing an artifact that relates the effectiveness of knowledge transfer and the personality of the project professional to promote the success of the project. The thesis was built on three studies. In Study 1, a Systematic Literature Review was carried out with the objective of mapping studies on knowledge transfer in project management and the evolution of their discussions. The data was collected in the Scopus and WoS databases, the results identified relevant research fields on the constructs researched. In this study, it was also possible to identify the research gap for Studies 2 and 3, that is, to create a more complete process model (Artifact) for transferring knowledge between projects and relate it to behavioral aspects of the project professional. The objective of Study 2 was to identify the scales of knowledge transfer in the area of project management and compare them to validate the appropriate scale for the study. A qualitative analysis of the scales found was carried out and a quantitative analysis was carried out using Survey questionnaires with the knowledge transfer effectiveness scale for 100 project professionals. Data were analyzed using Exploratory Factor Analysis (EFA) with Jamovi 1.6.23 software. Based on this scale validated in the Brazilian context, in Study 3 the mediating effect of the effectiveness of knowledge transfer between the personality of the project professional and the success of the project was tested. An empirical study was carried out with a quantitative approach using Survey questionnaires. Data were analyzed using partial least squares structural equation modeling (PLS-SEM). In the results, it was indicated that the personality trait of conscientiousness of the project professional has a direct impact on the dimensions of project success (project efficiency, project team and project client) and a partial mediation by the effectiveness of knowledge transfer at the project client. Subsequently, it was possible to develop the artifact that relates the effectiveness of knowledge transfer and the personality of the project professional to promote the success of the project. The three studies enabled the generation of a Technical / Technological Product – PTT (artifact). The tool helps to identify and understand the four professional profiles based on emotional stability for effective knowledge transfer, project professionals can improve their performance, contributing to the success of the project.